2013
DOI: 10.1186/1475-925x-12-48
|View full text |Cite
|
Sign up to set email alerts
|

An improved level set method for vertebra CT image segmentation

Abstract: BackgroundClinical diagnosis and therapy for the lumbar disc herniation requires accurate vertebra segmentation. The complex anatomical structure and the degenerative deformations of the vertebrae makes its segmentation challenging.MethodsAn improved level set method, namely edge- and region-based level set method (ERBLS), is proposed for vertebra CT images segmentation. By considering the gradient information and local region characteristics of images, the proposed model can efficiently segment images with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 33 publications
0
46
0
1
Order By: Relevance
“…A set S in Euclidean space is said to be convex if every straight-line segment having its two end points in S lies entirely in S. The smallest convex set that contains the entire point set is its convex hull which is described by the convex combination of finite subset of points in C, as given in Eq. (9).…”
Section: Contour Initialization Using α Hullmentioning
confidence: 99%
See 1 more Smart Citation
“…A set S in Euclidean space is said to be convex if every straight-line segment having its two end points in S lies entirely in S. The smallest convex set that contains the entire point set is its convex hull which is described by the convex combination of finite subset of points in C, as given in Eq. (9).…”
Section: Contour Initialization Using α Hullmentioning
confidence: 99%
“…For Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/cbm the spine [9], presents an algorithm which utilizes an edge detection function and region detection function to extract lumbar vertebrae for identifying disc herniation. This method is initialized with an Otsu threshold.…”
Section: Introductionmentioning
confidence: 99%
“…There exists a wide range of approaches in the existing literature for spine and vertebral segmentation [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20]. Table I lists the main papers and reported segmentation results on spine segmentation in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Manual delineation of spinal canal is a time consuming and tedious work, so studies trying to automate this task can be found in the literature [1], [2]. Another application where spine detection is fundamental is in spine segmentation [3], [4], and hence in biomechanical modeling [5] as well as computer-aided detection (CAD) [6]. Furthermore, precise spine detection allows performing curved planar reformation and enabling easier navigation and manipulation of spine in 3D [7].…”
Section: Introductionmentioning
confidence: 99%